OZONIOTERAPIA EM UM CANINO COM SUSPEITA DE POLIRRADICULONEURITE - RELATO DE CASO - Morais, Laura Eliza; Marder, Douglas Stum; Londero, Maria Janaina Rodrigues; Jappe, Roger Rambo (Salão do Conhecimento, 2019)
Relato de caso clínico